PELATIHAN BATIK CIPRAT UNTUK KOMUNITAS DISABILITAS SEBAGAI UPAYA UNTUK PENINGKATAN KEMANDIRIAN PEREKONOMIAN DI KABUPATEN REMBANG, JAWA TENGAH - Ardhani Putri, Hanuring Ayu; Khaerudin, Ary; Supratiwi, Mahardika; Rikah, Rikah; Rudianto, M. (LPPM ITB AAS Indonesia Surakarta, 2024)
This community service activity aims to provide training assistance in making splash batik made by people with disabilities in facing increasingly tight market competition in Sridadi Village, Rembang Regency. The method of providing training and discussion regarding the process of making splash batik. In general, activities consist of preparation, training, evaluation and marketing of splash batik made by people with disabilities. The implementation of this community service activity uses Continued direct practice of carrying out batik activities. The implications of this community service activity are the existence of good products, pricing strategies, promotional strategies, and distribution strategies even in the midst of various existing limitations, which have a direct impact on increasing sales and economically improving the welfare of our brothers and sisters with disabilities. Keywords: splash batik, people with disabilities, economic independence